2017
DOI: 10.4102/sajce.v7i1.553
|View full text |Cite
|
Sign up to set email alerts
|

How is their word knowledge growing? Exploring Grade 3 vocabulary in South African township schools

Abstract: In this article, we report on a study that examined the active and receptive English vocabulary of two different groups of Grade 3 learners in South African township schools. The groups consisted of English Home Language (HL) learners in the Western Cape and Xhosa HL and English First Additional Language (FAL) learners in the Eastern Cape. The purpose was to document their different vocabulary trajectories during Grade 3. The Woodcock-Muñoz Language Survey was used to measure the active vocabulary levels of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…In this study, the following important conditions for incidental vocabulary learning to occur were identified: emphasis on written English exposure in Grade 3 classrooms, rather than on oral exposure, and compliance with the sequential order of graded reading schemes. We know that learners in South African township schools are capable of increasing their active word knowledge by about 9% per year (Pretorius & Stoffelsma 2017). Through the current study, we are now beginning to understand what the opportunities are for incidental vocabulary exposure from graded readers and teacher talk.…”
Section: Implications For Policy and Further Researchmentioning
confidence: 84%
See 2 more Smart Citations
“…In this study, the following important conditions for incidental vocabulary learning to occur were identified: emphasis on written English exposure in Grade 3 classrooms, rather than on oral exposure, and compliance with the sequential order of graded reading schemes. We know that learners in South African township schools are capable of increasing their active word knowledge by about 9% per year (Pretorius & Stoffelsma 2017). Through the current study, we are now beginning to understand what the opportunities are for incidental vocabulary exposure from graded readers and teacher talk.…”
Section: Implications For Policy and Further Researchmentioning
confidence: 84%
“…One way to prepare learners for this linguistic challenge is to ensure that they have a sufficient level of English vocabulary by the end of Grade 3. A recent study found that English HL learners in Western Cape township schools had a receptive vocabulary knowledge of only 61% of the most frequent words by the end of Grade 3, whereas their English Foreign Additional Language (FAL) counterparts only knew 27% of these words (Pretorius & Stoffelsma 2017). This not only shows that there are vast differences between English HL and FAL learners, but it also shows that they are not adequately prepared for the vocabulary level of Grade 4.…”
Section: Vocabulary In Gradementioning
confidence: 99%
See 1 more Smart Citation
“…The language demands placed on learners are not taken seriously enough by CAPS , which results in the unrealistic expectation that students who cannot be assumed to “have any knowledge of the language when they arrive at school” are able to reach “a high level of competence in English by the end of Grade 3” (DBE, 2011b, p. 8) in a stipulated minimum of 180 curriculum hours and a maximum of 400. Both research (Macdonald, ; Pretorius & Stoffelsma, ; Sibanda, ) and PIRLS test results (Howie et al., ) have shown that these curriculum requirements are not attainable. English determines school success or failure, and anglonormativity (McKinney, ) remains unchallenged.…”
Section: Cohort Dropout Ratesmentioning
confidence: 99%
“…Children with a limited vocabulary not only lag behind their peers at school entry, but the gap widens as they progress through school. Pretorius and Stoffelsma ( 2017 ) found that a group English First Additional Language learners in the Eastern Cape only knew 27% of the most frequent words in their textbooks by the end of Grade 3.…”
Section: Introductionmentioning
confidence: 99%